Kebijakan Pembangunan Border Barrier di Wilayah Perbatasan oleh Hungaria sebagai Upaya Mengatasi Krisis Imigran - Mechiho, Samuel; Dharmiasih, D.A. Wiwik; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT             This research aims to describe what is the reason for Hungary has built a border barrier in the border region using descriptive qualitative methods. Hungary, which is a member state of the European Union, facing a contemporary security threat, which is the flow of immigrants. To cope with this issues, Hungary issued a physical development policy in the form of a border barrier. Although it did not get funding from the European Union in the process of building the border barrier, Hungary continued to carry out the construction process.Therefore, researchers use the framework of immigrant as a contemporary security threat and border barrier as a foreign policy to answer what is the reason for the construction of the border fences in the border region.   Keywords: Hungary, Contemporary Security Threat, Foreign Policy, Immigrant, Border Barrier